Testicular dysgenesis syndrome and phthalate exposure: A review of literature - Erkekoğlu, Pinar; Özyurt, Aylin Balcı; Yirün, Anıl; Çakır, Deniz Arca (Archives of Pharmacy, 2021)
Endocrine disruptors are chemicals that interfere with the body’s endocrine system and cause adverse effects in biological systems. Phthalates are a group of man-made chemicals which are mainly used as plasticizers and classified as endocrine disruptors. They are also used in cosmetic and personal care products as color or smell fixators. Moreover, phthalates are present in inks, adhesives, sealants, automobile parts, tools, toys, carpets, medical tubing and blood storage bags, and food packages. Pathological condition known as “testicular dysgenesis syndrome” (TDS) or “phthalate syndrome” is usually linked to phthalate exposure and is coined to describe the rise in alterations in reproductive health in men, such as reduced semen quality (decrease in sperm counts, sperm motility and increase in abnormal sperms), hypospadias, cryptorchidism, reduced anogenital distance and early-life testicular cancer. Phthalates are suggested to cause direct effect on gonadal and non-gonadal tissues, impair the differentiation and morphogenesis of seminiferous tubules and accessory sex organs and testicular cells (both Sertoli and Leydig cells), alter estradiol and/or testosterone levels, decrease insulin-like 3 (INSL3) peptide production, impair spermatogenesis and lead to epigenetic alterations, all of which may lead to TDS. This review will mainly focus on phthalates as causes of TDS and their mechanisms of action.